Risiko Pembiayaan Murabahah dan Musyarakah Pada Profitabilitas Bank Umum Syariah - Rivai, Afif (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2017)
This study aims to determine the effect of murabahah and musyarakah financing risk on the profitability of sharia commercial banks. The research method used in this research is the explanation method, that is to know or explain the influence between one variable to other variables The variables studied are variable x is murabahah financing risk and musyarakah financing risk, while variable y is profitability. Population used in this research is sharia commercial bank. The sample selection was done by purposive sampling technique. Based on the criteria, obtained 5 (five) syariah banks that become the sample of this study. Partially murabahah financing risks have a negative and significant effect on profitability and risk of musyarakah financing have a positive and significant impact on the profitability of sharia commercial banks. While the simultaneous murabahah and musyarakah financing risks have a positive and significant impact on the profitability of sharia banks.